Efficiency of cytokinin for propagation of Gluta usitata (Na-pong3) in vitro - Rakrawee, R.; Kittibanpacha, K.; Chareonsap, P. P.; Poeaim, A. (My University, 2018)
The result was explained an effect of Plant Growth Regulators (PGRs) for young seeds induction and shoot multiplication of Gluta usitata (Na-pong3) by plant tissue culture technique to preserve and increased plant propagation. The young seeds were induced by comparison to 0.5, 1, 1.5, 2 and 3 mg/L 6-Benzyl amino purine (BAP), Thidiazuron (TDZ) or meta-Topolin (mT) on Woody Plant Medium (WPM). The results showed the highest percentage of seed regeneration was 1.5 mg/L BAP which was100% germination. The shoots was highest induced by 0.5 mg/L BAP after culture for 6 weeks. The shoots were transferred to WPM medium containing with BAP, TDZ or mT for multiple shoot induction. The maximum number of shoots were observed on WPM medium combined with 1.5 mg/L BAP (about 6 shoots per explant) after subcultured for three to four times. The best of root induction was observed on WPM medium without PGRs.
Keywords: Gluta usitata; Shoot multiplication; Young seeds regeneration